A STUDY OF METAPHOR IN LEONY JARDINE’S POEMS “THE MOON AND HER SECRETS” - Diajeng Amelia Putri; Diana Sopha (PHILOLOGY Journal of English Language and Literature, 2026)
This study examines the use of metaphor in Leony Jardine’s poetry collection The Moon and Her Secrets. The research focuses on how metaphors—particularly structural, orientational, and ontological metaphors as conceptualized by Lakoff and Johnson (2003)—are employed to reflect psychological conflicts, emotional depth, and identity struggles. Using a qualitative descriptive method, this study analyzes selected poems through close reading, supported by Conceptual Metaphor Theory and a psychological literary approach. The findings reveal that Jardine consistently employs the moon as a central metaphor representing secrecy, vulnerability, and transformation. Ontological metaphors dominate, presenting emotions as concrete entities and allowing abstract experiences to be visualized. These results emphasize that Jardine’s poetry transforms metaphor into a primary medium for exploring inner conflict and self-discovery.